(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Cement dust is one of the major air pollutants and its exposure causes various problems. It has deleterious effect on vital organs and may affect liver function. This study was done to assess the effects of cement dust on liver function parameters of cement factory workers. Materials and methods: This case control study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram in collaboration with Heidelberg Cement Bangladesh Ltd. Chattogram during January 2018 to December 2018. For these, 30 cement exposed workers of Heidelberg Cement Bangladesh Ltd. aged between 20-45 years were included as case group. Age and sex matched 30 subjects were selected from office workers of Heidelberg Cement Bangladesh Ltd. and Chittagong Medical College as control group. To assess liver function 3 ml of venous blood was collected from each subject under aseptic precaution. Liver enzymes were assessed. After compiling data, statistical analyses were done by using SPSS for windows version-25. Unpaired student’s‘t’ test was done as test of significance. Results: Liver enzymes like serum AST and serum ALT was lower in case group than control group within normal range and it was not statistically significant. Serum ALT was significantly higher in case group than control. It was also within normal range. Conclusion: This study suggests that liver function might not be impaired by cement dust. Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 22-24